Faktor- Faktor Yang Berpengaruh Terhadap Hiperbilirubinemia Di RS Muhammadiyah Gersik: Factors Affecting Hyperbilirubinemia at Muhammadiyah Hospital Gersik - Cholifah, Cholifah (Jurnal Kebidanan Midwiferia, 2017)
Its complications can lead to jaundice with kern infant mortality. The incidence of hiperbilirubinemia in RSM Gersik there increased from september to October as much as 3.31% from 8.39% to 12%. For it to do research on the factors that influence on hiperbilirubinemia. Analytical research methods with a population of all babies who are in the space Crunch a number of RSM 137 babies baby on the 1st elementary school, November 30, 2016. Data taken using a data sheet of the recapitulation is then processed in a descriptive with cross tabulations and frequenciesare tabulated. Bivariat analysis test use Spearman'sRho. Multivariate analyses using Logistic Regression Analysis with error rate α = 0.05.The results showed nearly all babies in Muhammadiyah Gersik Hospital born aterm(93.4%), no asphyxia(95,6%),does not suffer the trauma of birth (gold 90.5%), normal infant birth weight(88,3%), not having the infection (94,9%) experienced nohypoglycemia(88,3%) and most of the babies did not experience bilirubinemia (93.4%).There is a gestation age relationship (P = 0.0001), infant birth weight (P = 0.0001) and infections (P = 0.0001) and hiperbilirubinemia. There is no relationship of trauma at birth (P = 0,318), asfeksia (P = 0422), and hypoglycemia (P = 0,312) with hiperbilirubinemia. There is no influence jointly between (the age of gestation, birth weight, infection) against hiperbilirubinemia at the Muhammadiyah Gresik.Expected community and health workers particularly thosestationed inthe space ofNeonatesto doearly detection ofrisks so thathiperbilirubinemiacan dothe anticipationfor the preventionand treatment ofHiperbilirubinemiain the newbornappropriately.